Improving management of duodenal ulcer disease. Issue 865 (November 1997) - Bateson, M. C.; Diffey, B. L.
Abstract : Audit of treatment of duodenal ulcer disease has allowed management to improve and keep abreast of rapid advances in care. Eradication of Helicobacter pylori was assessed by 14C urea breath test one to two months after anti-Helicobacter therapy. The old triple therapy regime of bismuth, tetracycline and metronidazole for two weeks was found to be toxic and of low effectiveness (82%). Regimes with lansoprazole for one month and antibiotics for one week gave 90-98% success rates. The best success has been with regimes containing both clarithromycin and a nitro-imidazole. There was complete success in 98% of 109 patients given quadruple therapy with lansoprazole 30 mg daily for one month plus tetracycline 500 mg twice daily, clarithromycin 250 mg twice daily and metronidazole 400 mg twice daily for one week.